An Alternative Specimen in Toxicological Analysis: Nail - Efeoğlu Özşeker, Pınar; Dağlıoğlu, Nebile (The Bulletin of Legal Medicine, 2018)
The use of alternative biological samples has increased with the development of sensitive and selective analytical techniques in recent days. Keratinous biological samples such as hair and nail have attracted the attention of clinical and forensic toxicologist when blood and urine sample especially were not taken in cases which were the decomposed and unfolded postmortem cases.Drugs, medicines, drug of abuse and heavy metals may accumulate for a long time in hair and nail. The nail sample may be useful for toxicological analysis when the hair sample, which is a good marker for past use, is inadequate. Sample preparation and analytical methods to be used are important because of the complex structure of nail and low drug concentration detected in nail.In this study, the basic structure of nail used as an alternative to toxicological analysis, the mechanism of drug or substance transfer into the nail, analytical methods, the advantages / disadvantages of nails and how to interpret the results will be examined.
Keywords: nail; toxicological analysis; interpretation